Abandono familiar y sus consecuencias en el estado emocional de un adulto mayor de 68 años de edad de la ciudad de Quevedo - Valdiviezo Teran, Daniela Denisse (2022)
The abandonment of the elderly is a common problem in Ecuador; From the cultural aspect, currently the perspective of the elderly is that of being an economic burden for the family, then the process of psychological intervention in a case of family abandonment and the consequences that this has can be observed. in the emotional state of an older adult, in which the system of central beliefs based on cognitive behavioral theory was worked on, results of psychometric batteries in charge of measuring the deterioration of the cognitive processes of the older adult, and others in charge of verify the existence of clinical symptoms of neurotic disorders, such as depressive and anxious symptoms, and their severity.